Effectiveness Of Baby Massage On The Increase Of Baby Weight Aged 6 - 12 Months In Gayaman Village, Mojoanyar District, Mojokerto Regency - Titiek Idayanti; Rina Widiyawati (Universitas STRADA Indonesia, 2020)
The study population was all babies aged 6-12 months who experienced underweight. Samples were taken using a total sampling technique of 28 respondents. Data were collected by observation and subsequently tested using paired t-test. The average change in respondents’ weight before and after the baby massage is 114 grams. Paired t-test results show ρ value = 0.011 (95% CI: -.2005 - -. 0281). ρ value = 0.011 < α = 0.05, indicating that H0 is rejected and H1 is accepted. Therefore, there is an effect of baby massage on baby growth aged 6-12 months in Gayaman Village, Mojoanyar District, Mojokerto Regency. It is recommended for health workers to provide health education regarding the way to do the right baby massage to support in providing knowledge and expertise to parents in doing baby massage independently at home to help to reach the optimal growth process, especially the baby’s weight gain.